Analisis Miskonsepsi Buku Teks Biologi Kurikulum 2013 Kelas X di SMAS Teladan Medan pada Materi Virus dan Monera - Ade Sekar Anggraini; Syarifah Widya Ulfa; Adyla Syukrhaini Marwi; Aulia Andin Kinanti; Putri Agustina Anggreni Arwira; Rifqi Khoir Afdan (Jurnal Dirosah Islamiyah, 2024)
Books are a key element in the education system that helps deliver the curriculum and facilitate the learning process of students and teachers. Books provide learning resources that are easily accessible and can be adapted to students' needs. It plays an important role in learning, curriculum, and instruction in developing countries like Indonesia. However, careless selection of books can cause misconceptions in students, which can affect learning outcomes. Therefore, it is important to choose books that suit the curriculum and are able to convey concepts appropriately. Various assessments have been proposed to assess the quality of textbooks, including clarity of concepts, relevance to the curriculum, and ability to increase students' enthusiasm for learning. Misconceptions often arise from textbooks that are incorrect and not in accordance with the established curriculum, so analysis needs to be carried out to update the book. Descriptive research methods were used to analyze misconceptions in the 2013 Curriculum class This research highlights the importance of choosing textbooks that are accurate and in accordance with curriculum standards to prevent student misconceptions in biology learning.